Insights into saline adaptation strategies through a novel halophilic bacterium isolated from solar saltern of Yellow sea - Yoo, Yeonjae; Lee, Hanbyul; Lee, Junghyun; Khim, Jong Seong; Kim, Jae-Jin (Frontiers in Marine Science, 2023)
Solar salterns were placed along the coast and were frequently left unattended after use. While many studies have isolated and identified microorganisms from hypersaline environments, their role and adaptation mechanisms are still unclear. Herein, we elucidated the role of halophiles in salt-polluted areas through the recently reported Halomonas getboli YJPS3-2 from the abandoned saltern. We analyzed the expression levels of genes in the YJPS3-2 strain to identify its adaptation mechanisms to high salinity environments, by representing the process from tidal flats to abandoned salterns with varying salinity gradients. The YJPS3-2 strain primarily overexpresses genes associated with ABC transport to adapt to hypersaline environments. Interestingly, the cheA gene, which recognizes changes in the surrounding, was the most upregulated, and it was also associated with the overexpression of the MS ring and T3SS mechanisms relating to the flagellar activity. The YJPS3-2 recognized the high salt concentration in its surroundings and attempted to accumulate compatible solutes that could withstand high osmotic pressure inside the cell to adapt to the high salinity environment. Furthermore, during this process, the YJPS3-2 strain removed surrounding pollutants and secreted secondary metabolites that could be utilized by neighboring organisms. Our results suggested that this halophilic bacterium has the potential to serve as a pioneering species for thriving the surrounding while adapting to saline environments.